2021
DOI: 10.1177/07417136211046960
|View full text |Cite
|
Sign up to set email alerts
|

Age and Social Background as Predictors of Dropout in Second Chance Education in Germany

Abstract: Second chance education (SCE) has been established to offer adults the opportunity to catch up on higher qualifications, for instance the eligibility to study. SCE often suffers from high dropout rates, but little is known about the reasons. This article investigates whether dropout rates depend on family background and age, and if so, why. Data from 3278 students at an institution of SCE in Germany who entered this institution between 2000 and 2016 are analysed using logistic path modelling. The results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…Age has been linked to school dropout in certain research studies. In higher education, older students departed school more frequently than younger students [16][17][18][19].…”
Section: Drop-out Determinantsmentioning
confidence: 99%
“…Age has been linked to school dropout in certain research studies. In higher education, older students departed school more frequently than younger students [16][17][18][19].…”
Section: Drop-out Determinantsmentioning
confidence: 99%
“…Grading is to be seen as a "social practice" in which a number of factors, including student behavior, normative orientations, and classroom procedures are evaluated (Filer, 2000;Lintorf, 2012). For second-chance education, it can be shown that -controlling for indicators of achievement 2 -previous school-type affiliation strongly influences grades in main subjects at the end of the first semester of academic SCE, and, indirectly, grade development in the following years (Schuchart & Schimke, 2021). Former Gymnasium students have an advantage over students from other school types.…”
Section: Summary and Research Questionmentioning
confidence: 99%
“…In the German context, we focus on the Zweiten Bildungsweg [second-chance education] (Harney, 2018, see Figure 1) which offers adults the opportunity to catch up on the eligibility to study. High drop-out rates of around 50% show that a large proportion of students fail to meet the requirements of academic SCE, among them many students who previously attended a non-academic type of school with low requirements (Schuchart & Schimke, 2021). In this article we explore the role that previous school type affiliations might play in success in later educational stages.…”
Section: Introductionmentioning
confidence: 99%
“…); therefore, teaching methods promoting active participation are the most suitable for them [6]. Also, measures need to be taken to prevent second-chance students' dropout, particularly among disadvantaged students, where the dropout rate is the highest [16,17]. Also, education in the field is important; early leavers should receive information about learning opportunities and about the ways in which second chance education can change their lives.…”
mentioning
confidence: 99%